2014
DOI: 10.1016/j.radonc.2014.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Dose distribution resulting from changes in aeration of nasal cavity or paranasal sinus cancer in the proton therapy

Abstract: Background and Purpose: Aeration in the nasal cavity and paranasal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Similar findings were recently published for the cohort of 20 patients treated with proton therapy for nasal cavity or paranasal sinus cavities . The air content in the cavities increased in 18 out 20 cases.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar findings were recently published for the cohort of 20 patients treated with proton therapy for nasal cavity or paranasal sinus cavities . The air content in the cavities increased in 18 out 20 cases.…”
Section: Discussionsupporting
confidence: 88%
“…We focused on dosimetric changes that might justify a need for adaptive proton planning. As it is well known, the proton ranges are very susceptible to changes in air cavities within radiation fields . Nevertheless, our study has shown that in most of the cases the coverage of target volumes was not compromised substantially even for the patients that were rescanned late in the course of treatment and for those who exhibited a pronounced change in aeration within the cavity.…”
Section: Discussionmentioning
confidence: 53%
“…A potential pitfall of this technique in sinonasal cancer treatment is the complex interaction between setup errors and anatomical uncertainties (ie, variations in nasal cavity and paranasal sinuses filling) that could occur during treatment with potential relevant differences between the nominal dose distribution (calculated on the planning CT) and the actual delivered dose [17]. In light of this, weekly verification CT scans with the implementation of 3-dimensional image-guided protocols in proton therapy [18] are recommended to establish the need for replanning.…”
Section: Discussionmentioning
confidence: 99%
“…However, further improvement in the local control of this disease using IMRT seems di cult due to contradiction between its need for high required radical dose to the tumor and the dose limits of the surrounding normal tissues. As a result, the dominance of IMRT is being challenged by a new charged particle radiotherapy mode, termed as proton beam therapy (PBT), which possesses superior dose distribution afforded by protons' "Bragg peaks" [5,6]. According to an authoritative systematical review, compared to IMRT, PBT has been found to improve the 5-year overall survival rate of paranasal sinus and nasal cavity cancer from 45.1% to 69.7% [7].…”
Section: Introductionmentioning
confidence: 99%